Carbon Nanotubes: Continuous Band‐Filling Control and One‐Dimensional Transport in Metallic and Semiconducting Carbon Nanotube Tangled Films (Adv. Funct. Mater. 22/2014). (June 2014) - Shimotani, Hidekazu; Tsuda, Satoshi; Yuan, Hongtao; Yomogida, Yohei; Moriya, Rieko; Takenobu, Taishi; Yanagi, Kazuhiro; Iwasa, Yoshihiro
<x xml:space="preserve">Abstract</x> H. Shimotani and co‐workers report the substantial changes in the conductance of a metallic SWNT thin film with an ionic‐liquid gating. On page 3305, number of current‐carrying subbands in metallic SWNTs as well as semiconducting SWNTs are electrochemically controlled and observed in situ with optical absorption spectrometer. The conductance of SWNT thin films shows stepwise increases when the number of current‐carrying subbands increases. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>